Cadherin-2 controls directional chain migration of cerebellar granule neurons. - Sandra Rieger; Niklas Senghaas; Axel Walch; Reinhard W Köster (PLoS Biology)
Long distance migration of differentiating granule cells from the cerebellar upper rhombic lip has been reported in many vertebrates. However, the knowledge about the subcellular dynamics and molecular mechanisms regulating directional neuronal migration in vivo is just beginning to emerge. Here we show by time-lapse imaging in live zebrafish (Danio rerio) embryos that cerebellar granule cells migrate in chain-like structures in a homotypic glia-independent manner. Temporal rescue of zebrafish Cadherin-2 mutants reveals a direct role for this adhesion molecule in mediating chain formation and coherent migratory behavior of granule cells. In addition, Cadherin-2 maintains the orientation of cell polarization in direction of migration, whereas in Cadherin-2 mutant granule cells the site of leading edge formation and centrosome positioning is randomized. Thus, the lack of adhesion leads to impaired directional migration with a mispositioning of Cadherin-2 deficient granule cells as a consequence. Furthermore, these cells fail to differentiate properly into mature granule neurons. In vivo imaging of Cadherin-2 localization revealed the dynamics of this adhesion molecule during cell locomotion. Cadherin-2 concentrates transiently at the front of granule cells during the initiation of individual migratory steps by intramembraneous transport. The presence of Cadherin-2 in the leading edge corresponds to the observed centrosome orientation in direction of migration. Our results indicate that Cadherin-2 plays a key role during zebrafish granule cell migration by continuously coordinating cell-cell contacts and cell polarity through the remodeling of adherens junctions. As Cadherin-containing adherens junctions have been shown to be connected via microtubule fibers with the centrosome, our results offer an explanation for the mechanism of leading edge and centrosome positioning during nucleokinetic migration of many vertebrate neuronal populations.